APPLICATION OF BIOAUGMENTATION TO SOLVE AMMONIA IN THE SEDIMENT OF THE CULTURE MEDIUM OF TIGER SHRIMP (Penaeus monodon F.) IN DIFFERENT SALINITIES - S. Sarjito (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Bioaugmentation was used to solve the ammonia problem, because this method is relatively safe to theenvironment. The objective of this research was to determine the influence and effectiveness ofbioaugmentation on the reduction of ammonia in the sediment in culture medium of Tiger shrimp (P.monodon). Laboratory scale experiment and splitted plot randomized design was performed. The maintreatment was probiotic epicin concentration of 0; 0.5; 1.0; and 1 ppm; as sub-treatment was the salinity(20; 25 and 30 ppt), and as a group was dayobservation (0; 2; 4 and 6). Sediment from intensive culturesystem was taken from brackish water pond of Brackishwater Aquaculture Development Project (BADP),Jepara. Sediment ammonia was analyzed using methods of Parson et al.,(1989). The research was conducted at hatchery of Fisheries and Marine Science Faculty of Diponegoro University, Teluk Awur, Jepara. The result indicated that bioaugmentation was able to reduce ammonia concentration in the sediment. Epicin has high significantly effected on the reduction of ammonia in the sediment (p<0.01). Thecapability of epicin as a bioaugmentation started on the day of 2. Therefore, the results also showed that a time (day) was highly significant affect on the reduction of ammonia in the sediment (p<0.01). However, salinity did not affect on the reduction of ammonia in the sediment (p>0.05). The most effective epicin dose to reduce ammonia in the sediment of the culture medium of Tiger shrimp (P. monodon) was 1.5 ppm.